INTERAKSI PEMBELAJARAN MENULIS PARAGRAF DEDUKTIF PADA MAHASISWA FKIP UNIVERSITAS TRIDINANTI PALEMBANG - Doni Samaya (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2019)
This research starts from the researchers’ observation that most students still haven't been able to write paragraphs correctly. During this time, students just write without regard to the concept of the right of the paragraph so that it causes a large number of errors in the writing of a paragraph especially deductive paragraph. This study aims to describe the interaction of the students with lecturers, students and lecturers. In addition, the study also aims to find out the factors that affect of the students in writing a deductive paragraph. Method of this research was using a combination of qualitative and quantitative. The collection of data in this study was conducted with the questionaire of enclosed, test the deductive paragraph writing performance, and useful observations. The questionqire closed spring results data would be presentation clearly; results of writing test data is described based on deductive paragraph writing assessment rubric by Oshima and Hogue (2006); data and observations are also useful is described clearly. Based on analysis of data researchers get results that 1) there were some factors which influence the students in writing deductive paragraph; 2) there were three learning interactions in writing deductive paragraph of students in FKIP Tridinanti University of Palembang.